2012
DOI: 10.1177/0017896912450875
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the medical school educational environment: Validating an approach from Saudi Arabia

Abstract: Objective: This study is an empirical analysis of the female students’ attitudes toward the medical educational environment and climate in the College of Medicine at King Khalid University. Setting: The Dundee Ready Educational Environment Measure (DREEM) questionnaire was administered on the same day to 100 female students studying in the third (pre-clinical), fifth and sixth (final) year at the College of Medicine, King Khalid University. Although the sample size was limited in size, it was deemed acceptable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 8 publications
1
15
2
Order By: Relevance
“…This is in agreement with a range of authors who have reported Cronbach’s alpha scores of 0.75 [28], 0.87 [5], 0.89 [29], 0.90 [6,30], 0.912 [31], and 0.93 [7,18,32,33]. This variability in alpha scores demonstrates the sample-dependent nature of the statistic and supports the need for authors to continue to investigate the psychometrics of the DREEM.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with a range of authors who have reported Cronbach’s alpha scores of 0.75 [28], 0.87 [5], 0.89 [29], 0.90 [6,30], 0.912 [31], and 0.93 [7,18,32,33]. This variability in alpha scores demonstrates the sample-dependent nature of the statistic and supports the need for authors to continue to investigate the psychometrics of the DREEM.…”
Section: Discussionsupporting
confidence: 93%
“…A reciprocal relationship is between the host organisation and the LE structure that is also evident in the 12 papers discussing the role of the host organisation. 51,53,62,68,77,79,80,85,86,90,91,102,104 The host organisation is responsible for supporting and overseeing activities stipulated within the curriculum. The host organisation has direct and indirect influence upon the LE structure.…”
Section: Le Structurementioning
confidence: 99%
“…The host organisation has direct and indirect influence upon the LE structure. 51,53,62,68,77,79,80,85,86,90,91,102,104 Direct influence of the host organisation upon the LE structure is primarily through the matching process and mentee and mentor training. 49,56,86,88,99,102,107 The host organisation also directly defines and oversees compliance of the roles, responsibilities and code of conduct of tutors and learners.…”
Section: Le Structurementioning
confidence: 99%
See 2 more Smart Citations